Creation of Composers - Basis of Music Culture - Tursunova Dilorom Dzhakhonovna (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
The composer has performed various tasks in the past. First, he is a creator of new, original melodies and songs. Secondly, the composer created their rhythmic and melodic variants on the topic of ready-made tunes. In the article, the author elaborated on the topic of the basis of composers' creativity-musical culture, and explained the history, origin and prospects of composition.